Osteoporotic Characteristics Persist in the Spine of Ovariectomized Sheep after Withdrawal of Corticosteroid Administration - Mohammad-Reza Zarrinkalam; Christopher G. Schultz; Ian H. Parkinson; Robert J. Moore (Journal of Osteoporosis)
A validated ovine model of osteoporosis achieves severe bone loss in a relatively short period. This study investigated if osteoporotic features persist in this model after cessation of corticosteroid administration. Methods. Osteoporosis was induced in nine ewes by chronic corticosteroid injection, ovariectomy, and low calcium diet. Six ewes were used as controls. Bone mineral density (BMD) of the lumbar spine (LS) and body weight were assessed at regular intervals. After five months, corticosteroid treatment was withdrawn systematically over one month. Three months later, all animals were euthanised, and the LS was collected for histomorphometric analysis. Results. BMD in the LS of osteoporotic sheep was 25% lower than control sheep. Body weight of osteoporotic sheep was reduced in the first month of the corticosteroid withdrawal period but returned to baseline level thereafter. Trabecular bone volume of LS in osteoporotic sheep was 27% lower than controls and showed a heterogeneous structure. Conclusions. Osteoporotic characteristics remain in the vertebra after ceasing corticosteroid administration providing an opportunity to evaluate potential systemic or local treatments in vivo under realistic physiological conditions. The microstructural arrangement of vertebral trabecular bone in sheep is similar to humans demonstrating further relevance of this model for preclinical investigations.